Robbing Behavior in Honey Bees - Ryan Willingham; Jeanette Klopchin; James D. Ellis (EDIS)
Western honey bee workers can invade and steal honey/nectar from other colonies or sugar/corn syrup from feeders used to deliver syrup to other colonies. This is called “robbing” behavior. Robbing behavior typically involves the collection of nectar and honey, but not pollen or brood. Some beekeepers report that robbing bees may steal wax or propolis from other hives, but there is not much data available on this occurrence. Robbing behavior can escalate quickly from just a few bees robbing other colonies to a massive frenzy of bees robbing many colonies in an apiary. This 3-page fact sheet was written by Ryan Willingham, Jeanette Klopchin, and James Ellis, and published by the UF Department of Entomology and Nematology, February 2015. (Photo Credit: UF/HBREL)